Pengaruh Problematika Mahasiswa Menikah Terhadap Aktivitas Belajar Program Studi Pendidikan Agama Islam Universitas Muhammadiyah Surakarta - Jamil, Rosyid Abdul; , Drs. Suharjianto, M.Ag; , Drs. Bambang Raharjo, M.Ag (2016)
ABSTRACT Students who are already faced with two different obligations, on the other hand the obligation to learn and liabilities in the household. Students who are married must be clever in managing the time between learning obligations and liabilities in the household. Students who are married if they are still active or not in college. As well as learning activities whether to decline or perhaps even more so because learning is compared with students who are not married who has no more responsibility than students who are married. Hence, this study is very interesting to study with the title Effect Problems Married Students Against Student Learning Activities Program of Islamic Education Muhammadiyah University of Surakarta. In this study, the considered problem is How the timing of students who are married to the learning activities. This study aims to find out how students who are married in organizing learning activities and the results of learning activities of students who are married. While the benefits can contribute scientific and intellectual repertoire, particularly about the completion of the problems of students of Islamic Education University of Muhammadiyah Surakarta married in setting the time to learn. Results are expected to be useful and valuable to add to the experience as well as references to the provision of face next life as well as the inputs that can be used as an unforgettable experience. This research is qualitative research subject is student class of 2011 married Studies Islamic Religious Education, Faculty of Islamic Studies, University of Muhammadiyah Surakarta. Method is a collection of data used documentation, questionnaires and interviews. While the data analysis methods used are interactive cycle analysis that takes data from the field, then summarize and correlating information from the data obtained and then a conclusion. Based on the results of research and data analysis, it can be concluded that students who are married in the timing of learning activities is still not good because there are some aspects of learning activities that are less qualified.